Tetralogy of Fallot with congenital diaphragmatic hernia with right lung aplasia—a rare entity - Arora, Yatin (Indian J Thorac Cardiovasc Surg, 2020)
A combination of tetralogy of Fallot with diaphragmatic hernia represents a very rare entity. We present a case of 18-month-old child presenting late with cyanosis and respiratory distress. Chest X-ray and computed tomography angiography showed tetralogy of Fallot with small left pulmonary artery with right lung aplasia with congenital diaphragmatic hernia with liver and bowel loops in right chest cavity. The patient was managed with central shunt on cardiopulmonary bypass and was discharged uneventfully.